A dietary survey of patients with irritable bowel syndrome. (9th May 2013) - Hayes, P.; Corish, C.; O'Mahony, E.; Quigley, E. M. M.
Abstract: Background: Food is one of the most commonly reported triggers of irritable bowel syndrome (IBS) symptoms. However, the role of diet in the aetiology and management of IBS has not been clearly established. The present study aimed to examine the dietary practices of Irish patients with IBS and to determine whether these practices increased their vulnerability to nutritional inadequacies. Methods: A questionnaire was completed by 135 IBS patients on their perceptions of the role of diet in their symptoms and whether they restrict their diet according to the symptoms experienced. A similar questionnaire was used to investigate the perceptions of 111 healthy subjects to the gastrointestinal symptoms experienced on the consumption of food. Results: Food was considered to cause or worsen their gastrointestinal symptoms in 89.6% of IBS patients compared to 55% of healthy subjects ( P < 0.001). Cereal‐based foods, predominantly bread or its components, were the most frequently cited (53.3%), and spicy foods (39.3%), vegetables and fatty foods (35.6% for both) also featured prominently. A significantly greater number of patients with IBS reported changing their diet to minimise symptoms compared to healthy controls (91.9% versus 45.5%, P < 0.001). In relation to whole food groups, milk products (9.6%), fruit (7.4%) and vegetables (5.2%) were those most commonly restricted, with only a small number of IBS patients seeking professional healthcare advice. Conclusions: The majority of IBS patients consider their symptoms to be related to food, and change their diet by limiting the foods that they perceive as problematic, with some restricting whole food groups. Few patients sought professional healthcare advice when implementing dietary change, possibly exposing a considerable number to an increased risk of nutritional deficiency.